(3GdUMjaI GdSLGOjIs - (3GdgGTej GdbQTj, CHh GdMSf, Rjf GdYGHOjf, Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, J (B94(3g` (B712(3es
(3ChdgG (B:s
(3ChdgG(B: (3MOKfG GdSjO GdCLd fLe GdOjf HgGA GdTQa CHh GdMSf eMeO Hf GdMSf Hf CMeO Hf Ydj Hf eMeO Hf YeQ Hf jMji GdYdhjs
(3BNQgG (B:s
(3BNQgG(B: (3abO CUHMJ hCfJ KbJj hQLGFj aj GdCehQ cdgG aGbV dj HNjQgG YGbHI hfLfj ef eVdGJ GdaJf HQMeJc jG CQMe GdQGMejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 277s
(3GdPQjYI, L (B15: 15s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs